Hubungan Pengetahuan Masyarakat tentang Covid-19 dengan Stigma Masyarakat terhadap Pasien Isolasi Mandiri Positif Covid-19 - Esti Nur Janah; Ariyanti; Awis Hamid Dani (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
The Covid-19 pandemic (Coronavirus Disease2019) caused by the SARSCoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) virus is an event that threatens public health in general and has attracted worldwide attention. In the midst of the Covid-19 outbreak, there is a social phenomenon that has the potential to exacerbate the condition of Covid-19, namely social stigma or negative associations for a person or group of people who experience symptoms or have certain diseases, are labeled, stereotyped, discriminated against, treated differently or experienced harassment status due to association with a disease. This study aims to determine the relationship between public knowledge about Covid-19 and the community's stigma against Covid-19 positive self-isolation patients in the village of Cilibur 2020. This research is a quantitative study with a cross-sectional design. Data collection began in October-December 2020 for 109 respondents who were taken by total sampling technique. Primary data collection is obtained from interviews using questionnaires and checklists. Analysis of the data obtained using univariate to describe the characteristics of respondents, univariate analysis and bivariate analysis using the Spearman rank test. There is a significant relationship between knowledge and community stigma in Cilibur Village, Paguyangan District. This is indicated by the results of the study that the statistical test results obtained a sig (2-tailed) value of 0.002